Islamic Perspective on Assets and Property - Hamzah, Halipah; Saiti, Buerhan; Saefurrohman, Ghina Ulfah; Uluyol, Burhan (Human Resource Management Academic Research Society, 2023)
The riches and possessions Allah SWT gives to His followers are entirely His property. Humanity's presence in this world is simply a temporary loan, and all other creatures are free to use it in beneficial ways. According to Islamic beliefs, there are numerous methods for transferring property and wealth, including zakat, almsgiving, loans, debts, waqf, wills, donations, and the like. The Quran, hadith, journals, books, and proceedings connected to assets and wealth according to Islamic perspectives were analysed using a content analysis design in this qualitative study, which was then reported in descriptive form. This study tries to determine the degree to which Muslims handle their property and assets in accordance with Islamic requirements. The findings of this study are anticipated to inform the Muslim community that Allah SWT is the true owner of all things and that humans are merely trustees. How people manage and govern their assets and possessions determines their advantages or disadvantages.
Keywords: Assets; Property; Expenditure; Islamic Perspective